How does a diagnosis of mild cognitive impairment impact everyday behaviours, quality of life and healthcare utilisation? A systematic review of people with MCI and their carers. (20th December 2022) - Connolly, Evie Margaret; Slight, Sarah; Ardle, Ríona Mc
Abstract: Background: The UK National Dementia Strategy was developed to improve professional and public attitudes and understanding around dementia, and to ensure through all stages of dementia that patients receive high‐quality care and support (1) . Mild cognitive impairment (MCI) is a prodromal stage of dementia that can impact on patients' everyday behaviours and quality of life (QOL). Carers may undertake additional responsibilities, which may ultimately impact on their health. We conducted a systematic review on the impact of an MCI diagnosis on the lives of both the individual and carers/families, focusing on everyday behaviours, QOL, and healthcare utilisation. Method: This systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews (PRISMA) checklist. We searched five large databases including Web of Science, Scopus, Medline, Embase and Psychinfo for studies published after Jan 2004, using appropriate key terms. Titles, abstracts and full texts were screened against set inclusion criteria. Data were extracted onto a customized data extraction sheet, and a narrative synthesis of all eligible studies was undertaken. This review was registered with PROSPERO (no CRD42021291995). Results: Ten papers were included. Patients diagnosed with MCI and cares/families described a lack of understanding of the term MCI itself, particularly around 'mild' and the anxiety around further cognitive decline. There was a perceived lack of information provided to both patient and carers around the diagnosis, with carers not perceiving themselves as carers up until that point. Carers also reported increased levels of depression and distress as they undertook more caring responsibilities. Carers experienced frustration with loved ones, who denied that they had memory problems and took longer to process and do things; this led to increased family conflict. Conclusion: This review identified the functional and psychosocial impact of a MCI diagnosis on people and carers. There is a critical need to combat stigma, increase information and support for people with MCI, and provide psychosocial interventions for people and carers post MCI diagnosis to enhance them to better cope and potentially reduce related depression, anxiety, and carer burden. 1 Banerjee S. Living well with dementia–development of the national dementia strategy for England. Int J Geriatr Psychiatry. 2010;25:917‐922.